Pengaruh Kepemimpinan, Pelatihan, Dan Pengembangan Karir Terhadap Kinerja Karyawan Pada Destinasi Wisata Beejay Bakau Resort Kota Probolinggo - Putri, Mayang Lutfiasari; Elmas, Muhammad Syarif Hidayatullah; Tumini, Tumini (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The role of a leader in a company is to be the main figure who controls the successful performance of a company. Competition is getting tighter day by day so companies are required to have strategies to improve employee performance, one of which is at the BeeJay Bakau Resort Tourist Destination, Probolinggo City. This research aims to determine whether or not there is a relationship between Leadership, Training and Career Development on Employee Performance, either simultaneously, partially or dominantly. The method used in this research is quantitative with a sample size of 38 respondents, all employees at the BeeJay Bakau Resort Tourism Destination, Probolinggo City. The results of this research are the first to show that there is a significant simultaneous influence between Leadership, Training and Career Development variables on Employee Performance at the BeeJay Bakau Resort Tourism Destination, Probolinggo City. Second, there is a partially significant influence between the Leadership, Training and Career Development variables on Employee Performance at the BeeJay Bakau Resort Tourism Destination, Probolinggo City. And third, the Leadership variable has a dominant influence on Employee Performance at the BeeJay Bakau ResortTourism Destination, Probolinggo City.